Measurement of advanced glycation end products could be used as an indicator of unhealthy nutrition for colorectal cancer risk - Şahingöz Erdal, Gülçin; Yaman, Mustafa; Yıldırım Servi, Esra; Uğur, Halime; Kasapoğlu, Pınar; Çikot, Murat; Işıksaçan, Nilgün (Routledge Journals, Taylor & Francis Ltd, 2022)
The main culprit behind most cancers is the accumulation of reactive oxygen species. Glyoxal (GO) and methylglyoxal (MGO) are reactive intermediates created by food processing and they are precursors of advanced glycation end products (AGE) that cause glycative stress. We aimed to evaluate the relationship between AGE levels of healthy volunteers and treatment-naive patients diagnosed with colorectal cancer. The study consisted of patients diagnosed with colorectal cancer and healthy volunteers who underwent routine colonoscopy. The study was conducted with a total of 42 cases, 47.6% (n = 20) female. The ages of the participants in the study ranged from 41 to 82 years, and the mean was 60.57 +/- 10.78 years. The GO and MGO values of the patient group were found to be significantly higher than those of the control group (p = 0.007, p = 0.001, respectively). The risk of colorectal cancer was 22 and 57 times higher in individuals with GO and MGO values above 1.25 mu g/mL and 0.0095 mu g/mL, respectively. The blood AGE level is closely related to diet, and it can be decreased through the appropriate improvement of diet. Thus, the measurement of AGE can be used to predict whether a person's nutrition is healthy or unhealthy and prevent increased risk of colorectal cancer.
Keywords: Colorectal Cancer Risk; Unhealthy Nutrition; Measurement of Advanced Glycation